The role of proinflammatory cytokines in the comprehensive treatment of patients with diabetic foot syndrome complicated by osteomyelitis - Yuri G. Lutsenko; Igor S. Karabak; Igor B. Andrienko; Kirill S. Karabak (Consilium Medicum)
Background. Diabetic foot syndrome (DFS) complicated by osteomyelitis is a severe consequence of diabetes mellitus, often leading to amputations. Chronic inflammation and cytokine imbalance (interleukin – IL-1β, 6, tumor necrosis factor – TNF-α) play a key role in pathogenesis, making the search for immunomodulatory therapies, such as ozone therapy (OT), highly relevant.